Fibre Bragg Grating and No-Core Fibre Sensors - Daud, Suzairi (SpringerBriefs in Physics,, 2018)
This book focuses on the development and set-up of fibre Bragg grating (FBG) and no-core fibre (NCF) sensors. It discusses the properties of the sensors and modelling of the resulting devices, which include electronic, optoelectronic, photovoltaic, and spintronic devices. In addition to providing detailed explanations of the properties of FBG and NCF sensors, it features a wealth of instructive illustrations and tables, helping to visualize the respective devices' functions.